The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1063/1.466786
|View full text |Cite
|
Sign up to set email alerts
|

Structural modifications in the amino acid lysine induced by soft x-ray irradiation

Abstract: The amino acid DL-lysine has been investigated using the surface-sensitive probe XPS (x-ray photoelectron spectroscopy). The XPS data confirm that solid-state lysine exists in the zwitterionic form. However, during the course of x-ray irradiation in the experiment, the molecule was observed to decompose. A decomposition mechanism consistent with the data has been proposed which involves transformation of the zwitterion to a free base, followed by decarboxylation, to produce 1,5-diaminopentane and CO2 gas. It w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
30
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 10 publications
6
30
1
Order By: Relevance
“…The strong chemical shift of þ2.3 eV towards higher binding energy indicates the acquisition of a strong positive charge localised at the N9 nitrogen atom, and unambiguously confirms formation of a salt with C --NH þ , in agreement with the crystal structure. 18 A comparable binding energy shift is observed in XPS studies of amino acids, [23][24][25][26] in which intramolecular transfer of the proton from the carboxylic acid to the amine group occurs. These results reveal strong evidence that probing the chemical state of acceptor and donor atoms in a molecular crystal with two components allows unequivocal distinction whether a salt or a co-crystal have been formed.…”
Section: Resultsmentioning
confidence: 52%
“…The strong chemical shift of þ2.3 eV towards higher binding energy indicates the acquisition of a strong positive charge localised at the N9 nitrogen atom, and unambiguously confirms formation of a salt with C --NH þ , in agreement with the crystal structure. 18 A comparable binding energy shift is observed in XPS studies of amino acids, [23][24][25][26] in which intramolecular transfer of the proton from the carboxylic acid to the amine group occurs. These results reveal strong evidence that probing the chemical state of acceptor and donor atoms in a molecular crystal with two components allows unequivocal distinction whether a salt or a co-crystal have been formed.…”
Section: Resultsmentioning
confidence: 52%
“…Experiments on amino acids are a natural starting point, since these molecules are comparably small, but still very important as the building blocks of most biologically relevant macromolecules. While amino acids have been studied intensively with soft X-ray techniques in the solid state [49][50][51][52][53][54][55][56][57][58] and the gas phase [54,[59][60][61][62], only a small number of experiments have been performed in solution, most of them studying a liquid jet with XAS or photoelectron spectroscopy [9,[63][64][65]. Beside the results presented here (see also [35]), only one other study using X-ray emission spectroscopy of glycine solutions has been published to date [9].…”
Section: Amino Acid Solutionsmentioning
confidence: 89%
“…For instance, it was found that soft x-ray irradiation of several amino acids under ultrahigh vacuum (UHV) conditions leads to a decomposition of the molecules via several pathways, including dehydrogenation, decarboxylation, deamination, and dehydration. [14][15][16][17][18][19][20] So far, little is known on the radiation-induced processes in mixed glycine-water ice films. Only very recently, Lattelais et al 21 reported on the effect of soft x-ray irradiation of glycine diluted into water ice at 30 K. On the basis of the x-ray absorption spectroscopy examinations, it was found that water neither protects nor enhances the glycine photodecomposition.…”
Section: Introductionmentioning
confidence: 99%